2002
DOI: 10.1016/s0169-328x(02)00187-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of mRNAs for microtubule disassembly molecules during nerve regeneration

Abstract: The mRNA expression of the microtubule disassembly molecules (SCG10, stathmin, SCLIP and RB3) in response to nerve injury was examined using a rat hypoglossal nerve injury model. After nerve injury prominent increase in mRNA expression of SCG10, stathmin and RB3 was observed, while only slight increase in SCLIP mRNA was observed in injured motor neurons. The increase in SCG10 and RB3 mRNA expression was quicker than that of stathmin and SCLIP. All the elevated signals decreased gradually to control levels by 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Indeed, Grenningloh et al (2004) report that overexpression of stathmin, a protein that increases the frequency of microtubule tip catastrophes, increases axon extension. In addition, proteins that regulate microtubule tip dynamics are up regulated during regeneration (Iwata et al, 2002). Second, our results are conceptually consistent with the \push" and \pull" model of axon extension (Letourneau et al, 1987).…”
Section: E14 Axon Extension In the Absence Of F-actin Requires Microtsupporting
confidence: 85%
“…Indeed, Grenningloh et al (2004) report that overexpression of stathmin, a protein that increases the frequency of microtubule tip catastrophes, increases axon extension. In addition, proteins that regulate microtubule tip dynamics are up regulated during regeneration (Iwata et al, 2002). Second, our results are conceptually consistent with the \push" and \pull" model of axon extension (Letourneau et al, 1987).…”
Section: E14 Axon Extension In the Absence Of F-actin Requires Microtsupporting
confidence: 85%
“…Previous studies have demonstrated that stathmin is expressed in mitotically active cells such as cancer cells, crypt cells in the intestinal epithelium, and hepatic epithelial cells after partial hepatectomy (20,23,47,48). Increased expression of stathmin has been shown to be associated with the reentry of the cells into the cell cycle and the onset of cell proliferation (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…41 However, RB3 is upregulated in peripheral nerve regeneration 39,42 and SCG10 and SCLIP are induced throughout the sprouting response in peripheral nerve. 44 Similarly, gene expression for p21 and SPRR1 are induced throughout the duration of the peripheral nerve sprouting response 43 unlike their transient induction in the region of poststroke axonal sprouting in peri-infarct cortex. 41 These differences between PNS and CNS postinjury axonal sprouting may reflect true differences in the molecular response of these two systems, and may account for the limited ability of the CNS to sprout.…”
Section: Growth Promotionmentioning
confidence: 99%